Improving Collaboration Skills of Students in Class V through Math Puzzle Games at UPT SDN 066054 Medan - Amaliyah, Putri; Syamsuyurnita, Syamsuyurnita; Revolina, Silsia Risqha (azkiya, 2024)
Students are less enthusiastic when given tasks in groups. They are not used to dividing tasks and roles in their discussion groups because they are not used to collaborating in their discussion groups. At the same time, collaboration skills are critical in 21st-century learning. From the problems found, a Classroom Action Research (PTK) was conducted to find out the improvement of collaboration skills of class V UPT SDN 066054 Medan students through math puzzle games on the material of FPB and KPK. The treatment results over two cycles showed a significant increase in collaboration skills. In the pre-cycle, the percentage of students' collaboration skills was 53%. Furthermore, the sample was given treatment by working on math puzzle games in groups so that the percentage of students' collaboration skills in cycle I increased by 28% to 81%, and in cycle II also increased by 8% to 89%. Thus, it can be concluded that puzzle games positively and effectively impact students' collaboration skills in mathematics subjects.